2011
DOI: 10.2147/opth.s19455
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of external and endoscopic endonasal dacryocystorhinostomy for acquired nasolacrimal duct obstruction

Abstract: PurposeTo compare success rates of external dacryocystorhinostomy (DCR) and endoscopic endonasal DCR for acquired nasolacrimal duct obstruction (NLDO).DesignHistorical cohort study.Participants100 patients who underwent external DCR and 105 patients who underwent endoscopic endonasal DCR.MethodsA retrospective review of medical records of patients with acquired NLDO who underwent DCR from 2004–2010 was performed. Data regarding the lacrimal drainage system, eye examination, surgical outcomes, patient symptom c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
100
1
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 34 publications
8
100
1
7
Order By: Relevance
“…Similarly, Watts et al (2001) reported a success rate of 94.7% in 19 patients at 12 months and Mirza et al (2002) reported a success rate of 94% in 49 patients after a mean follow-up of 9 months. All the surgeons in the above studies were highly experienced, with at least 10 years of experience in ophthalmology (Watts et al, 2001;Mirza et al, 2002;Besharati et al, 2005;Karim et al, 2011). In a study similar to ours, Besharati et al (2005) reported success rates of 88% in 149 patients in a teaching hospital in Iran, with a follow-up range of 3 months to 2 years.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Similarly, Watts et al (2001) reported a success rate of 94.7% in 19 patients at 12 months and Mirza et al (2002) reported a success rate of 94% in 49 patients after a mean follow-up of 9 months. All the surgeons in the above studies were highly experienced, with at least 10 years of experience in ophthalmology (Watts et al, 2001;Mirza et al, 2002;Besharati et al, 2005;Karim et al, 2011). In a study similar to ours, Besharati et al (2005) reported success rates of 88% in 149 patients in a teaching hospital in Iran, with a follow-up range of 3 months to 2 years.…”
Section: Discussionmentioning
confidence: 57%
“…Karim et al (2011) performed external DCR on 100 patients and reported an anatomical surgical success rate of 91%, with a complication rate of 4.7%, after a follow-up of 6 months. However, only 81.6% of patients had symptomatic relief.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complications of the endonasal approach tend to be more severe and include wound infection, bruising, scarring and punctual ectropion. [20] Intraoperative complications of the endonasal approach are orbital fat prolapse, retrobulbar hemorrhage and cerebrospinal fluid leakage. Moreover, postoperative complications include epistaxis, medial rectus palsy, progressive closure of the ostium, development of adhesions, granuloma formation, orbital/subcutaneous emphysema, hematoma, synechia, canalicular stenosis and conjunctival fistula.…”
Section: Discussionmentioning
confidence: 99%
“…Ašarų latakų, akiduobės, akių vokų uždegiminių ligų operacijose kraujavimo rizika yra didelė [28,29]. Tačiau nėra įrodymų, kurie leistų patvirtinti ar atmesti didesnę kraujavimo riziką okuloplastinių operacijų metu pacientams, vartojantiems antikoaguliantus ar antiagregantus [30,31].…”
Section: Tyrimo Objektas Ir Metodikaunclassified